Impedance measurement system simulation for trapped cell model in various microwell geometries - Sorawit Sanin (2020)
© Published under licence by IOP Publishing Ltd. Single cell analysis is a measurement or detection of individual cell properties and responses. The method is of significance due to stimulated responses of any individual cell are different depending on their morphology and functionality. Therefore, detected properties from a group of cells cannot be used to represent that of the individual cell. Since cells can move freely in a microfluidic system, a trap must be added to the system to fix the cell position at the detection region for long period observation and assay. One of the most popular used cell trap in the biomedical field is a microwell array. A sensitive technique for measuring single cell properties is an impedance measurement, in which small change in electrical properties of the cell and the surrounding medium between excitation and pick-up electrodes is recorded. However, the microwell placed between two electrodes acts as an electrical insulator to reduce the signal passing through the system. This paper focuses on the effect of microwell geometry parameters generated from the design of experiments (DOE) software on detected signals using finite element simulation software. The study found that the microwell wall thickness affects the detected current signal most significantly and the optimized geometry that minimally reduces measured current signal was 20 m height, 5 m well thickness, and 16 m gap size.